An open-globe injury case caused by brown bear attack - Ami Konno; Akihiro Ishibazawa; Hiroyuki Kagokawa; Yuuki Meya; Taiji Nagaoka (American Journal of Ophthalmology Case Reports)
Purpose: To document a case of open-globe injury (OGI) caused by a brown bear attack that resulted in a favorable structural and visual outcome. Observations: A 40-year-old Japanese female was transported by ambulance due to OGI with a choroidal hemorrhage in the right eye, resulting in light perception (LP) visual acuity following a brown bear attack. We pursued a two-stage approach, commencing with primary posterior scleral wound repair and an encircling scleral buckle. On postoperative day 17, the patient underwent drainage of the choroidal hemorrhage and pars plana vitrectomy combined with cataract surgery. After the vitreoretinal surgery, visual acuity improved from LP to 20/60. Conclusions and importance: OGIs may result in severe visual impairment, and in the worst case, enucleation. We hypothesize that primary encircling scleral buckle and vitreoretinal surgery in a two-stage approach are factors contributing to a favorable structural and visual outcome. There are no reports of good visual acuity following a brown bear attack. Preoperative surgical planning and appropriate intraoperative re-assessment are crucial.